Drug resistant TB – latest developments in epidemiology, diagnostics and management - Tiberi, Simon; Utjesanovic, Natasa; Galvin, Jessica; Centis, Rosella; D'Ambrosio, Lia; van den Boom, Martin; Zumla, Alimuddin; Migliori, Giovanni Battista (International journal of infectious diseases, 2022)
•DR- and MDR-TB are more frequent in contacts and patients previously treated.•Whole genome sequencing, rapid, consistent and sensitive, is very useful in outbreaks•RR/MDR-TB requires treatment with ≥4 drugs for 6–24 months.•An all oral shorter WHO course is now recommended for the treatment of RR-TB.•Pulmonary rehabilitation is useful for patients with sequelae. The aim of this review is to inform the reader on the latest developments in epidemiology, diagnostics and management. Drug-resistant Tuberculosis (DR-TB) continues to be a current global health threat, and is defined by higher morbidity and mortality, sequelae, higher cost and complexity. The WHO classifies drug-resistant TB into 5 categories: isoniazid-resistant TB, rifampicin resistant (RR)-TB and MDR-TB, (TB resistant to isoniazid and rifampicin), pre-extensively drug-resistant TB (pre-XDR-TB) which is MDR-TB with resistance to a fluoroquinolone and finally XDR-TB that is TB resistant to rifampicin, plus any fluoroquinolone, plus at least one further priority A drug (bedaquiline or linezolid). Of 500,000 estimated new cases of RR-TB in 2020, only 157 903 cases are notified. Only about a third of cases are detected and treated annually. Recently newer rapid diagnostic methods like the GeneXpert, whole genome sequencing and Myc-TB offer solutions for rapid detection of resistance. The availability of new TB drugs and shorter treatment regimens have been recommended for the management of DR-TB. Despite advances in diagnostics and treatments we still have to find and treat two thirds of the drug resistant cases that go undetected and therefore go untreated each year. Control of TB and elimination will only occur if cases are detected, diagnosed and treated promptly.